The Influence of Microenvironment on Survival of Intraportal Transplanted Islets - Yan, Ling-ling; Ye, Li-ping; Chen, Ya-hong; He, Sai-qin; Zhang, Chen-yang; Mao, Xin-li; Li, Shao-wei (Frontiers in Immunology, 2022)
Clinical islet transplantation has the potential to cure type 1 diabetes. Despite recent therapeutic success, it is still uncommon because transplanted islets are damaged by multiple challenges, including instant blood mediated inflammatory reaction (IBMIR), inflammatory cytokines, hypoxia/reperfusion injury, and immune rejection. The transplantation microenvironment plays a vital role especially in intraportal islet transplantation. The identification and targeting of pathways that function as “master regulators” during deleterious inflammatory events after transplantation, and the induction of immune tolerance, are necessary to improve the survival of transplanted islets. In this article, we attempt to provide an overview of the influence of microenvironment on the survival of transplanted islets, as well as possible therapeutic targets.